EFFECT OF ZINC STRESS ON BIOCHEMICAL PROFILING IN DUNALIELLA SALINA TEOD. AND SPIRULINA PLATENSIS GOMO: Life Science -Botany - PAL SINGH, GAJENDRA; KUMAR, MANOJ; DAIYA, AMRIT (International Journal of Life Science and Pharma Research, 2018)
All biomolecules like lipids, carbohydrates and fatty acid compositions of a native microalgae Dunaliella salina (Teod.) and Spirulina platensis (Gomo.) were studied in batch culture at light intensity 100 µ mol photons m-2 s-1 temperature 25 ± 1oC and 16:8 h light and dark diurnal cycles. It was reported in our previous paper that both lipids and carbohydrate content decreased with increasing concentration of Cu stress. Similar scenario of contents was observed in lipid and carbohydrate on various treatment doses of zinc as heavy metal. GC-MS profiling of lipids showed that various compounds separated according to their retention time in which most of the compounds were Fatty Acid Methyl Ester. Further, purification of carbohydrates was confirmed by HPLC analysis using reference compounds like fructose, glucose and sucrose. The microalgae is rich deposits of essential nutrients so they could be candidate for aqua-culture feeding and/or biofuel production.